2018
DOI: 10.1044/2018_jslhr-s-17-0392
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Lexical Status and Individual Differences for Perceptual Learning in Younger and Older Adults

Abstract: Perceptual learning in younger and older adults 2 Abstract Purpose: This study examined whether older adults remain perceptually flexible when presented with ambiguities in speech in the absence of lexically disambiguating information. We expected older adults to show less perceptual learning when top-down information was not available. We also investigated whether individual differences in executive function predicted perceptual learning in older and younger adults.Method: Younger (n=31) and older adults (n=2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 49 publications
5
22
1
Order By: Relevance
“…Previous studies have shown that listeners show different degrees of lexically-guided perceptual learning [12] [17], which was also demonstrated in our behavioral results. To investigate whether the observed change in amplitude between pretest and posttest reflected lexically-guided perceptual learning, the size of the ERP effect was correlated by subjects with the degree of learning observed in the behavioral task.…”
Section: Correlating the Behavioral And Eeg Datasupporting
confidence: 89%
See 2 more Smart Citations
“…Previous studies have shown that listeners show different degrees of lexically-guided perceptual learning [12] [17], which was also demonstrated in our behavioral results. To investigate whether the observed change in amplitude between pretest and posttest reflected lexically-guided perceptual learning, the size of the ERP effect was correlated by subjects with the degree of learning observed in the behavioral task.…”
Section: Correlating the Behavioral And Eeg Datasupporting
confidence: 89%
“…It has been argued that focusing listeners' attention on the ambiguity of a sound will inhibit this type of learning [9] [19]. However, despite employing a phonetic categorization task at pretest and posttest which focused participants' attention on the ambiguous nature of the sound stimuli, we observed a clear lexically-guided perceptual learning effect, similar to [7] [17], in about half of our participants. These results show that lexically-guided perceptual learning can take place under conditions where ambiguity is made explicit to the listener.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Sensitivity to distributional variation in the input does not cease after the infant has acquired the phonetic inventory of a language (Clayards, Tanenhaus, Aslin, & Jacobs, 2008;Theodore & Monto, 2019). Instead, functional plasticity is observed across the life span such that listeners dynamically modify the mapping to speech sounds in line with statistical distributions of acoustic-phonetic cues in the input (e.g., Colby, Clayards, & Baum, 2018;Norris, McQueen, & Cutler, 2003;Theodore & Monto, 2019).…”
mentioning
confidence: 99%
“…Relatively less is known about factors that influence individual differences in distributional learning for the earliest stages of language comprehension, including the stage in which listeners map speech acoustics to consonants and vowels. Colby et al (2018) recently examined whether individual differences in receptive vocabulary, working memory, 1…”
mentioning
confidence: 99%